The Bluefin Tuna Fishery in the Bay of Biscay Its Relationship with the Crisis of Catches of Large Specimens in the East Atlantic Fisheries from the 1960s - Cort, José Luis; Abaunza, Pablo (SpringerBriefs in Biology, 2019)
This open access book is an original contribution to the knowledge on fishing and research associated with one of the most enigmatic fish of our seas: bluefin tuna, Thunnus thynnus (L.). Based on available evidence, it reconstructs the possible methods used to catch large spawners in the Strait of Gibraltar thousands of years ago and describes the much more recent overfishing that led to a great reduction in the catches of the trap fishery on the area and the disappearance of the northern European fisheries. It is the first book to relate the overfishing of juvenile fishes in certain areas to the decline of large spawners in other very distant areas, revealing one of the main underlying causes of this decline, which has remained a mystery to the fishing sector and scientists alike for over 50 years. This finding should serve to prevent similar cases from arising in the future.